PENGARUH MINAT BELAJAR, PERHATIAN ORANG TUA, DAN KINERJA GURU TERHADAP PRESTASI BELAJAR IPS SISWA - Sarmin dan Buchory M.S (Universitas PGRI Yogyakarta, 2015)
The purpose of research to determine the effect of Interest in Learning, Attention Parents and Teachers Performance against IPS Student Achievement in ElementarySchool Class V Se-District of Wonosobo regency Sapuran academic year 2013/2014. Thestudy population was a fifth grade students Sapuran Elementary School District ofWonosobo, amounting to 976 students with a sample of 100 students. The technique ofcollecting data using questionnaires and documentation. Analysis of data using multipleregression analysis three predictors. The results showed that there was a significantpositive influence and interest in learning, attention of parents, teachers and theperformance of the IPS Student Achievement in Elementary School Class V Se-Districtof Wonosobo regency Sapuran academic year 2013/2014. Effective contribution Interestin Learning, Attention Parents and teacher performance to student achievement of 90.8%.